Hacking The Geneology and Typology of Reforming Malay-Nusantara Islamic Thought In Singapore's Al-Imam Magazine (1906-1908) - Alimuddin Hassan Palawa; Agus Miftakus Surur; Dardiri Husni; Masbukin A Rajab; Asmuri Asmuri (NALAR: Jurnal Peradaban dan Pemikiran Islam, 2023)
Al-Imam is the first magazine in Persada Alam Melayu-Nusantara that promotes the renewal of Islamic thought and voices the awakening of the backwardness and stagnation of Muslims in this region in the first decade of the 20th century. The managers of Al-Imam magazine claim to be students of Sheikh al-Imam Muhammad Abduh and Rashid Ridha. Thus, in terms of spirit, material, and publishing format, Al-Imam magazine is a